2000
DOI: 10.1208/ps020212
|View full text |Cite
|
Sign up to set email alerts
|

Light-scattering investigations on dilute nonionic oil-in-water microemulsions

Abstract: Dilute 3-component nonionic oil-in-water microemulsions formulated with either a polyoxyethylene surfactant (C 18:1 E 10 or C 12 E 10 ) or the alkylamine-N-oxide surfactant, DDAO (C 12 AO), and containing either a triglyceride or an ethyl ester oil have been examined using dynamic and static lightscattering techniques. Analysis of the results showed distinct differences in the tested oil's mode of incorporation into the microemulsion droplets, with both the molecular volume of the oil and the hydrophobic chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 12 publications
(14 reference statements)
4
27
0
Order By: Relevance
“…This may be attributed to the fact that the addition of cosurfactant may lead to greater penetration of the oil phase in the hydrophobic region of the surfactant monomers, thereby further decreasing the interfacial tension, which leads to an increase in the fluidity of the interface to take up the different curvatures required to form nanoemulsions over a wide range of compositions. 2,7 The dose of ramipril varies between 2.5 mg and 20 mg; a frequently prescribed adult dose is 5 mg. Therefore, for the present study, a 5-mg dose was selected for the development of the nanoemulsion formulation.…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to the fact that the addition of cosurfactant may lead to greater penetration of the oil phase in the hydrophobic region of the surfactant monomers, thereby further decreasing the interfacial tension, which leads to an increase in the fluidity of the interface to take up the different curvatures required to form nanoemulsions over a wide range of compositions. 2,7 The dose of ramipril varies between 2.5 mg and 20 mg; a frequently prescribed adult dose is 5 mg. Therefore, for the present study, a 5-mg dose was selected for the development of the nanoemulsion formulation.…”
Section: Resultsmentioning
confidence: 99%
“…The Inhibitory Phase-It has been reported that C 12 E 10 forms spherical micelles in aqueous solutions (45). When bilayerforming long-chain lipids are mixed with these detergent molecules, the two components mix to form mixed micelles with a similar size (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…It may be due to further reduction of the interfacial tension, increasing the fluidity of the interface, thereby increasing the entropy of the system. There may be greater penetration of the oil phase in the hydrophobic region of the surfactant monomers (21,22). As we further increased surfactant concentration in S mix to 2:1 (Fig.…”
Section: Pseudo-ternary Phase Diagrammentioning
confidence: 93%